2003
DOI: 10.1002/anie.200351210
|View full text |Cite
|
Sign up to set email alerts
|

Serine Octamer Reactions: Indicators of Prebiotic Relevance

Abstract: The earliest molecule of life? Chirally selective reactions relevant to the origin of homochiral life are undergone by serine. Chiral exchange between serine, glyceraldehyde, and glucose occurs, favoring the enantiomers (L‐serine, D‐sugars) present in modern living systems (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 21 publications
5
111
0
Order By: Relevance
“…Briefly, these studies show that serine octamers undergo chiroselective substitution reactions in which serine molecules in the homochiral octamer are replaced by other amino acids or sugars, resulting in mixed serine/amino acid and serine/saccharide noncovalently-bound clusters. These reactions favor the enantiomers present in living systems, which supports the idea that homochiral serine octamers might have been involved in prebiotic mechanisms that led to the accumulation and transmission of homochirality [44,46,63].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Briefly, these studies show that serine octamers undergo chiroselective substitution reactions in which serine molecules in the homochiral octamer are replaced by other amino acids or sugars, resulting in mixed serine/amino acid and serine/saccharide noncovalently-bound clusters. These reactions favor the enantiomers present in living systems, which supports the idea that homochiral serine octamers might have been involved in prebiotic mechanisms that led to the accumulation and transmission of homochirality [44,46,63].…”
supporting
confidence: 70%
“…Various research groups have studied clusters of this amino acid using both ESI and SSI mass spectrometry , motivated by earlier studies which showed that the formation of protonated serine octamers occurs with a remarkably strong preference for homochirality [37][38][39][40][41]. The chemistry of the ionized serine octamer in the presence of compounds of biochemical significance, such as other coding amino acids, sugars, phosphoric acid, and transition-metal cations, has also been investigated [44,46,63]. Briefly, these studies show that serine octamers undergo chiroselective substitution reactions in which serine molecules in the homochiral octamer are replaced by other amino acids or sugars, resulting in mixed serine/amino acid and serine/saccharide noncovalently-bound clusters.…”
mentioning
confidence: 99%
“…Recently, the study of biomolecular cluster cations has become an active research field, and much work has dealt with the formation, dissociation, and charge partitioning among fragments of protein cluster cations [5][6][7][8][9][10]. Magic numbers for amino acid cationic clusters [11][12][13] and preference for homochirality [14,15] have been reported. Negatively charged clusters of amino acids have also been produced [13].…”
mentioning
confidence: 99%
“…That it gave D-GLA dominance instead of L-GLA dominance can be characterizes by a morphological principle, which one can describe as "self-stabilizing coincidence". But once the D-GLA dominance was established the effect of chiral discrimination with the amino acids ensured a bio-organic environment of D-GLA and L-amino acids [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…But L-Serine is especially interesting because it exhibits chiral discrimination in diluted aqueous solutions and forms clusters with D-GLA [17], and it exhibits corresponding chiral discrimination with other L-amino acids [18] whereby it establishes the stereospecific link between D-sugars and L-amino acids in aqueous solutions.…”
Section: Chiral Discriminationmentioning
confidence: 99%